VALLS, RAFAEL (2008). La enseñanza de la Historia y textos escolares. Buenos Aires: Editorial Libros del Zorzal, 108 páginas. - García, Natalia (Revista Fuentes, 2011)
Reseña sobre VALLS, RAFAEL (2008). La enseñanza de la Historia y textos escolares. Buenos Aires: Editorial Libros del Zorzal, 108 páginas.